A Policy Proposal for Heritage Language Conservation: A Case for Indonesia and Sarawak - Suwarno, Bambang (Issues in Language Studies, 2017)
Heritage languages are declining in Indonesia and Sarawak. They need conservation due to their situations as endemic languages. Their decline could be attributed to the fact that they often do not possess significant roles in the public domains. As a result, their speakers see little rewards or prestige for maintaining them. In Indonesian and Malaysian constitutions there is a spirit for protecting heritage languages. However, their executions, through national laws, might not have provided adequate protection for the heritage languages. As heritage languages keep declining, a policy revision needs to be given consideration. A heritage language may better survive if it has some functions in the public domains. Thus, to conserve the heritage languages, there is a need for the revision of language policy, so that these languages may have roles in the public domains, with varying scope, depending on their size. Large regional languages may be given maximum roles in the public domains, while smaller regional languages may be given smaller roles. Language conservation areas could be developed, where heritage languages serve as co-official languages, besides the national language. These areas may range from a district to a province or a state.